Comparison of Microwave Induced and Conventional Synthesis of Caffeine and Structural Characterization of Synthetic Products - Džudžević Čančar, H.; Dedić, A.; Mandal, Š.; Alispahić, A. (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2018)
Caffeine (1,3,7-Trimethylxanthine) is a purine alkaloid present in numerous plants (green/black tea leaves, coffee, cocoa). Since most conventional organic reactions are long-lasting and take place at very high temperatures using toxic solvents, alternative methods such as microwave (MW) assisted synthesis are increasingly used. Both conventional and MW-induced methods for the preparation of caffeine from theobromine by SN2 reaction mechanism with NaOMe as a base and MeOH as a solvent are reported here. Conventional synthesis lasted 60 min under 50-60°C with a caffeine yield of around 80%. MW-induced synthesis under 29, 56 and 71°C lasted 2-5 min, yielding 80.48-92.93% caffeine. The best results were obtained under MW synthesis at 56°C with water as a solvent. Purity of all samples was confirmed by TLC and melting point determination. FTIR spectra of all samples showed remarkable agreement with the caffeine standard spectrum.